Can a Bonus Overcome Moral Hazard? An Experiment on Voluntary Payments, Competition, and Reputation in Markets for Expert Services - Vera Angelova; Tobias Regner (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2017)
Interactions between players with private information and opposed interests are often prone to bad advice and inefficient outcomes, e.g. markets for financial or health care services. In a deception game we investigate experimentally which factors could improve advice quality. Besides advisor competition and identifiability we add the possibility for clients to make a voluntary payment, a bonus, after observing advice quality. We observe a positive effect on the rate of truthful advice when the bonus creates multiple opportunities to reciprocate, that is, when the bonus is combined with identifiability (leading to several client-advisor interactions over the course of the game) or competition (allowing one advisor to have several clients who may reciprocate within one period).
Keywords: C91; D03; D82; G20; I11; 330; Asymmetric information; principal-agent; expert services; deception game; sender-receiver game; reciprocity; reputation; experiments; voluntary payment; competition